2019
DOI: 10.1016/j.mex.2019.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Natural radionuclides and radiological risk assessment of granite mining field in Asa, North-central Nigeria

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 22 publications
2
25
1
Order By: Relevance
“…The soils originate from the metamorphic and igneous rocks (basement complex rocks) which is nearly 95%. The quartzite augitegnesiss, banded gnesiss, biotite gnesiss, and granitic gnesiss are the major constituents of the metamorphic rocks [21][22][23][24][25][26] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The soils originate from the metamorphic and igneous rocks (basement complex rocks) which is nearly 95%. The quartzite augitegnesiss, banded gnesiss, biotite gnesiss, and granitic gnesiss are the major constituents of the metamorphic rocks [21][22][23][24][25][26] .…”
Section: Methodsmentioning
confidence: 99%
“…43.5% of these populations are children between 0 and 14 years, 53.3% are between 15 and 64 years and 3.2% are older people above 64 years 20 . On the geology of the study area, Ilorin consists of Pre-Cambrian basement complex with elevation that ranges between 273 and 333 m in the West harboring an isolated hill called Sobi hills which is about 394 m above sea level, and ranges between 200 and 364 m in the East 4 , 21 , 22 . Some part of Ilorin town is reportedly underlain by sedimentary rock, which consists of laterites and alluvial deposits 23 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal component of radiation is terrestrial gamma radiation which originates chiefly from the radioactive decay of natural potassium, radium, and thorium [4], [5]. These elements are widely distributed in terrestrial materials including soil, rocks, and building material extracted from the earth crust [6], [7], [8]. Epidemiological studies have shown that exposure to enhanced degree of background radiation of terrestrial origin is associated with somatic and genetic health effects that are detrimental to vital organs of the human body which can occasionally lead to death overtime [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Information on the level of radiation and distribution of radioelements such as 238 U, 234 Th, and their respective progenies together with the nonseries 40 K in the environment gives very important radiological baseline submission. Such submission is crucial in the understanding of man's exposure to ionizing radiation and useful in instituting radiation protection laws [6], [7], [8]. Assessment of public rate of exposure to ionizing radiation possibly due to changes in environmental radioactivity due to anthropogenic activities [11], [12] or geogenic processes is important.…”
Section: Introductionmentioning
confidence: 99%